Adolescents' and young adults' physical activity related to built environment - Cocca, Armando (2015)
Objectives. This study aims to analyse physical activity (PA) levels of high school and university students; to estimate their perception of built environment with regard to physical PA; and to assess the relation between PA and built environment. Methods. A sociological cross-sectional study with non-experimental design was applied. The International Physical Activity Questionnaire and the Built Environment Characteristics Questionnaire were filled in by a sample of 1.862 students from high schools and the university in Granada, Spain. Results. High school students were significantly more active than university students, the latter reaching insufficient levels of PA. Nevertheless, they consider Granada as a good context for carrying out outdoor exercise. No relations were found between PA levels and built environment. Conclusion. The discrepant outcomes for PA levels and perceived built environment suggest the need of interventions focused on making youth aware of the possibilities that an environment provides to them for exercising. Consequently, environment could have an impact on their health at the same time as youth learn to respect it.